2012
DOI: 10.5455/aim.2012.20.99-102
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Left Ventricular Size to Left Atrial and Left Atrial Appendage Size in Sinus Rhythm Patients with Dilated Cardiomyopathy

Abstract: Introduction:Thromboembolic events are a frequent cause of mortality in patients with congestive heart failure. The aim of or study was to evaluate the relationship of left ventricular end diastolic diameter (LVEDD) to left atrial (LA) size and left atrial appendage (LAA) size in patients with dilated cardiomyopathy in sinus rhythm, as well as to determine the prevalence of thrombi in LV and LA /LAA.Methods:This was a prospective cross-sectional study, conducted from December 2009 until December 2011. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…In a study from Eastern Europe involving 95 patients, the authors found that left ventricular end diastolic diameter correlated significantly with LA diameter (r=0.47), LA area (r=0.49) as well as volume (r=0.45) 4 . Mean LA diameter of the patients in that study was 46.02±5.07 mm 4 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study from Eastern Europe involving 95 patients, the authors found that left ventricular end diastolic diameter correlated significantly with LA diameter (r=0.47), LA area (r=0.49) as well as volume (r=0.45) 4 . Mean LA diameter of the patients in that study was 46.02±5.07 mm 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Mean LA diameter of the patients in that study was 46.02±5.07 mm 4 . In present study, the mean LA diameter was 43.95±5.38 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations